Ultrasonic-Assisted Extraction (UAE) for enhanced recovery of bioactive phenolic compounds from cosmos caudatus leaves - Abdul Latiff, Norliza; Pei, Ying Ong; Abdullah, Luqman Chuah; Abd Rashid, Siti Nor Azlina; Mohd Fauzi, Noor Akhmazillah; Mohd Amin, Noor Amaiza (2021)
Cosmos caudatus (C. caudatus) is one of the common medicinal plants and among the valuable plants that are high in bioactive compounds such as phenolics. In this study, an ultrasound-assisted extraction (UAE) method was used to optimise the extraction of bioactive compounds from C. caudatus leaves using response surface methodology (RSM) and employing a Box-Behnken experimental design (BBD). The extraction efficiency of UAE under the optimal extraction conditions was compared with the Soxhlet method. Also, an anti-microbial analysis against two human pathogenic bacteria; Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) was also evaluated. The effect of the extraction conditions was studied and optimised such as the solid-liquid ratio (10 to 30 g/ml), particle size (180 to 850 μm) and extraction time (20 to 30 min). Quercitrin and total phenolic content (TPC) were the selected response variables in this study. Based on the ANOVA analysis, the response surface model to predict the optimum yield of quercitrin and TPC was adequate with a high R-square value corresponding to 0.9930 and 0.9962. The optimal UAE conditions were 1:28 (g/mL), by using a particle size of 485 μm and an extraction time of 30 min, respectively. Remarkably, UAE reduced the extraction time and solvent volume, with the maximal recovery of bioactive compounds at a high antioxidant activity as compared with that of the Soxhlet method. The plant extract also exhibited potential microbial agents. Due to the above findings, UAE can be used to enrich quercitrin and total phenolic content from C. caudatus leaves. It also opens the possibility of plant extract to be used as an affordable component in many applications such as food formulations and anti-microbial agents.